Feasibility Study of a Municipality Solid Waste Incineration Plant in Jordan - Abu-Hijleh, B.A/K (1998)
The rapid growth in Jordan’s population coupled with an increasing standard of life, has resulted in a large increase of household and commercial waste. Environmental and health concerns as well as the high cost of establishing and maintaining adequate new landfills, has prompted serious thoughts of alternative methods for dealing with the increasing amount of waste. This paper focuses on the prospect of building a waste incineration plant that can be used to generate electricity and recycle material in Jordan. Sensitivity analyses of the plant profitability under several financing scenarios were performed. The results show that such a plant is economically feasible in Jordan.